2015
DOI: 10.4040/jkan.2015.45.1.118
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Characteristics of Chemotherapy-related Cognitive Impairment in Patients with Breast Cancer

Abstract: Purpose: Evidence suggests that some patients with breast cancer experience cognitive difficulties following chemotherapy. This longitudinal study was done to examine the prevalence of cognitive impairment and trajectory of cognitive function over time in women with breast cancer, who received adjuvant chemotherapy. Methods: Participants were 137 patients with breast cancer. They completed neuropsychological tests and the Functional Assessment of Cancer Therapy-Cognitive Function before adjuvant therapy (prete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 28 publications
1
11
0
4
Order By: Relevance
“…[13] As several studies have shown, memory impairment is the most prominent presentation of chemotherapy-induced cognitive impairment (CICI) in patients with breast cancer, [2,4,5] and acts as an important factor affecting the long-term quality of life in these patients. [6] …”
Section: Introductionmentioning
confidence: 99%
“…[13] As several studies have shown, memory impairment is the most prominent presentation of chemotherapy-induced cognitive impairment (CICI) in patients with breast cancer, [2,4,5] and acts as an important factor affecting the long-term quality of life in these patients. [6] …”
Section: Introductionmentioning
confidence: 99%
“…A maioria dos estudos explorou, além das funções executivas, outros domínios cognitivos e sintomas concomitantes ao processo da avaliação (Ando-Tanabe, 2014, Askren et al, 2014Chen et al, 2013;Dumas, 2013;Ganz et al, 2003;Jansen, 2011;Kam et al, 2016;Kesler et al, 2011;Koppelmans et al, 2012;Lyon et al, 2016;McDonald et al, 2013;Miao et al, 2016;Park et al, 2015;Piccirillo, et al, 2015;Yao et al, 2016;Zheng et al, 2014). Apenas Kam et al (2016), Miao et al (2016) e McDonald et al (2013) delimitaram-se à investigação e discussão aos aspectos relevantes do funcionamento executivo.…”
Section: Resultsunclassified
“…Partindo para os resultados das pesquisas que aplicaram baterias de testes neuropsicológicos, a maioria dos subdomínios que correspondem às funções executivas mostraram-se alteradas em grupos de mulheres com câncer de mama em condição de quimioterapia (Chen e al., 2014;Ganz et al, 2003;Koppelmans, 2012;Lyon et al, 2016;Park et al, 2015;Yao et al, 2016;Zheng et al, 2014). Corroborando com esses dados, Askren et al (2014), Dumas (2013), Kam et al (2016), Kesler (2011;, Miao et al (2016), McDonald et al (2013) e Piccirillo et al (2015, ao examinarem imagens de ressonância magnética, observaram alterações em ligações funcionais nas redes cerebrais no que se refere à função executiva.…”
Section: Resultsunclassified
See 2 more Smart Citations